Milk production on N fertilized grasslands versus grass-legumes pastures, grazed, continuosly or rotationally (Revista da Faculdade de Medicina Veterinária e Zootecnia da Universidade de São Paulo, 1982)
Twelve lactating cows, similar in size and production, were distributed in a completaly randomized block design, to a 2x2 factorial schedule of treatments as follows: A) Rhodes grass (Chloris gayana) with 100 kg/N/ha, continuously grazed; B) Same than A, rotationally grazed; C) Rhodes grass consorciated with perennial soybean (Glicine wightii), continuously grazed; D) Same than C, rotationally grazed. All treatments had 3,3 cows/ha, and the daily individual milk production and daily weight gains were, respectively : A = 8,9 kg and 0,360 kg; B = 9,6 kg and 0,767 kg; C = 7,2 kg and 0,380 kg; D = 7,8 kg and 0,066 kg. Statistical analysis showed significant differences (p < 0,05) favouring the N fertilized pastures, under any type of management. The research was run in the months of November, December and January, for 8 consecutive weeks, after a preliminary period of 21 days.